Up from the projects : an autobiography - Williams, Walter E. (Walter Edward), 1936-2020 (Hoover Institution Press publication., 2010)
"From his lower-middle-class beginnings in a mixed but predominantly black neighborhood in West Philadelphia to his department chairmanship at George Mason University, the life of Walter E. Williams is an "only in America" story of achievement. In Up from the Projects, this nationally syndicated columnist and prolific author recalls some of the highlights and turning points of his life."--Back cover